2017
DOI: 10.1038/srep46464
|View full text |Cite
|
Sign up to set email alerts
|

The BMP2 nuclear variant, nBMP2, is expressed in mouse hippocampus and impacts memory

Abstract: The novel nuclear protein nBMP2 is synthesized from the BMP2 gene by translational initiation at an alternative start codon. We generated a targeted mutant mouse, nBmp2NLStm, in which the nuclear localization signal (NLS) was inactivated to prevent nuclear translocation of nBMP2 while still allowing the normal synthesis and secretion of the BMP2 growth factor. These mice exhibit abnormal muscle function due to defective Ca2+ transport in skeletal muscle. We hypothesized that neurological function, which also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 54 publications
2
9
1
Order By: Relevance
“…Alternatively, it may be that the effects of nBMP2 deficiency in the nucleus are simply cumulative, causing a Ca 2+ -handling phenotype that becomes progressively more severe as cells differentiate and mature. A progressive phenotype is consistent with our previously reported observation that hippocampal long-term potentiation (LTP) was normal in 3-week-old nBmp2NLS tm mutant mice but deficient in 3-month-old mice 3 . Progressive impairment of intracellular Ca 2+ response has received attention recently as a potential mechanism for both brain and muscle aging 36–38 , suggesting that nBMP2 dysfunction could contribute to premature aging or aging-related diseases.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Alternatively, it may be that the effects of nBMP2 deficiency in the nucleus are simply cumulative, causing a Ca 2+ -handling phenotype that becomes progressively more severe as cells differentiate and mature. A progressive phenotype is consistent with our previously reported observation that hippocampal long-term potentiation (LTP) was normal in 3-week-old nBmp2NLS tm mutant mice but deficient in 3-month-old mice 3 . Progressive impairment of intracellular Ca 2+ response has received attention recently as a potential mechanism for both brain and muscle aging 36–38 , suggesting that nBMP2 dysfunction could contribute to premature aging or aging-related diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we demonstrated that deficiency of nBMP2 in the nucleus impairs secondary immune response as evidenced by diminished spleen enlargement, poor clearance of S. aureus from the bloodstream, and increased mortality after secondary infection 11 . We have also shown that deficiency of nBMP2 in myonuclei is correlated with slowed skeletal muscle relaxation after contraction, and deficiency of nBMP2 in the nuclei of hippocampal neurons is correlated with learning/memory deficits 2,3 . Each of these phenotypes is consistent with deficiencies in intracellular Ca 2+ transport, but until now, no direct measurements of intracellular Ca 2+ have been performed in cells from nBmp2NLS tm mutant mice.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations